Hydro-biogeochemical coupling beneath a large polythermal Arctic glacier: implications for subice sheet biogeochemistry - Jemma Wadham; Martyn Tranter; A.J. Hodson; Richard Hodgkins; S. Bottrell; Richard Cooper; R. Raiswell (2010)
We analyze the interannual chemical and isotopic composition of runoff from a large, high Arctic valley glacier over a 5 year period, during which drainage evolved from a long-residence-time drainage system feeding an artesian subglacial upwelling (SGU) at the glacier terminus to a shorter-residence-time drainage system feeding an ice-marginal channel (IMC). Increased icemelt inputs to the SGU are thought to have triggered this evolution. This sequence of events provides a unique opportunity to identify coupling between subglacial hydrology and biogeochemical processes within drainage systems of differing residence time. The biogeochemistry of the SGU is consistent with prolonged contact between meltwaters and subglacial sediments, in which silicate dissolution is enhanced, anoxic processes (e.g., sulphate reduction) prevail, and microbially generated CO2 and sulphide oxidation drive mineral dissolution. Solute in the IMC was mainly derived from moraine pore waters which are added to the channel via extraglacial streams. These pore waters acquire solute predominantly via sulphide oxidation coupled to carbonate/silicate dissolution. We present the first evidence that microbially mediated processes may contribute a substantial proportion (80% in this case) of the total glacial solute flux, which includes coupling between microbial CO2-generation and silicate/carbonate dissolution. The latter suggests the presence of biofilms in subglacial/ice-marginal sediments, where local perturbation of the geochemical environment by release of protons, organic acids, and ligands stimulates mineral dissolution. These data enable inferences to be made regarding biogeochemical processes in longer-residence-time glacial systems, with implications for the future exploration of Antarctic subglacial lakes and other wet-based ice sheet environments.